Developing emergency medical care policy across Kenya: A framework for policy development - Zoe Siegel; Trina Swanson; Emily Nyagaki; Adam R. Aluisio; Benjamin W. Wachira (African Journal of Emergency Medicine)
Background and objectives: The Kenya Emergency Medical Care (EMC) Policy 2020–2030 was created to guide the advancement of EMC throughout Kenya. This report describes and maps the ongoing EMC policy development process across Kenya's 47 counties, serving as a real-world example of EMC policy development within a decentralized healthcare system in a low—or middle-income country (LMIC). Methods: This report evaluates the development of county-specific EMC policies using the Kenya Institute for Public Policy Research and Analysis (KIPPRA) six stages for policy development: 1) problem identification, 2) agenda setting, 3) policy design, 4) approval, 5) implementation, and 6) monitoring and evaluation. Meeting minutes, workshop proceedings, and draft and final EMC policy documents were used to analyze the policy development process and provide a snapshot of current EMC policy statuses by county. Results: As of August 2024, 23 counties have engaged in EMC policy development. Thirteen have finalized and are implementing their EMC policies, while 10 await approval. The remaining 24 counties are still in the planning stages. This process included gathering baseline emergency medical care standards to identify areas for improvement in each county. A core vision, mission, and goal aligned with the national policy were established and tailored to the county's needs. County-specific strategies were developed to address gaps between the existing system and national objectives. EMC policies were drafted, collaboratively reviewed, revised, and finalized before official approval. The next steps will be implementation, monitoring, and evaluation. Growth and improvement will be measured post-implementation based on baseline EMC metrics. Conclusion: Kenya's strategy for EMC policy development across the 47 counties, utilizing KIPPRA's guidelines for public policy formulation, established a structured approach that included engaging stakeholders, conducting situational analyses, and aligning policy objectives with national goals. It is a comprehensive example of developing EMC policies for LMICs within decentralized healthcare systems.